New Methods of Testing and Evaluation (R&E-SOURCE, 2017)
In this study I introduce, that in addition to traditional testing methods such as oral tests, achievement tests, the assessment of various written works (graphic design, projects, protocols of measurements, etc.), at present other methods of testing and evaluation are applied as well, in particular: In this paper I introduce the differentiating and selective function of educational evaluation, which is oriented towards the differentiation of students in terms of their abilities, interests, or opportunities to advance to higher-level schools and to gain higher qualifications. I pointed out that it is often the subject of criticism because our schools usually only deepen the social inequalities among students, are selective about them and the choice of school is often determined by the result of school evaluation. By analyzing the functions of educational evaluation we aimed to arrive at defining the dimensions of educational evaluation that offer insight into the process, resources, methods of evaluation from different perspectives – the dimensions. In this paper, I define three dimensions of educational evaluation: the personality dimension, where the levels of relationships between the object and the subject of educational evaluation are examined, the didactic dimension, the aim of which is to optimize the process of teaching and learning through the function of feedback, and the social dimension, the point of which is to enrich evaluation with the achievements of modern science, technology and social relations.